Time-delay-integration CMOS image sensor design for space applications - Yu, Hang (2016)
In recent years, remote imaging systems have been used for a wide range of applications in geological exploration, oceanography, meteorology, military reconnaissance, etc. Differing from the normal cameras, the remote imaging systems capture still scene with the camera in uniform motion. Limited by the system moving velocity, only a short integration time is allowed, which will result in a low signal-to-noise ratio (SNR) in dark illumination conditions. Therefore, time-delay-integration (TDI) image sensors are widely applied. In an integration-mode TDI image sensor, the active pixels are placed in more than one row (stage) in across-track direction, with the pixel stages perpendicular to the image sensor movement direction (along-track direction). When the camera system moves at a constant velocity, the pixels are exposed to the same scene stage by stage and the panoramic image in the along-track direction is thus produced. As a result, each pixel stage has contribution to the optical integration, so the effective integration time and the signal strength are enhanced. For the multi-pixel-stage integration mechanism of TDI, the charge-coupled devices (CCDs) offer an effective solution. In CCD image sensors, the photo charge is stored in the potential well of the original pixel following integration, and then transferred out row by row. Meanwhile, the charge of the same column yet different rows can be added together during the transfer operation with higher efficiency. Accordingly, CCDs can perform TDI operation without any external support. Consequently, CCDs still have the largest share of the TDI image sensor market, even though complementary metal-oxide-semiconductor (CMOS) image sensors have increased in popularity in recent years.